2017
DOI: 10.1186/s12959-017-0135-3
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cardiac function and risk of venous thromboembolism in Asian countries

Abstract: Patients with reduced cardiac function are thought to have a higher risk of venous thromboembolism (VTE). Additionally, they are vulnerable to complications of pulmonary embolism (PE) as well as right heart failure (HF), which in return is supposed to increase the rate of mortality. Studies focusing on VTE in heart failure patients were rare in Asian countries before the 21st century. Nowadays, more and more data are becoming available in this field in Asia. It is already known that heart failure can increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 55 publications
(61 reference statements)
0
11
0
2
Order By: Relevance
“…Основными патогенетическими механизмами повышения риска ВТЭО у госпитализированных пациентов с сердечно-сосудистой патологией могут быть эндотелиальное повреждение и эндотелиальная дисфункция, нарушение работы антикоагулянтной системы протеина С при повышенной концентрации в плазме провоспалительных цитокинов (интерлейкин-6, фактор некроза опухоли и др. ), активация PAR-рецепторов, стаз крови в условиях снижения сердечного выброса, повреждение тканей с экспрессией тканевого фактора, запускающего коагуляционный каскад, замедление фибринолиза [10]. Дополнительными факторами риска ВТЭО при ХСН могут являться: пожилой возраст, иммобилизация, инфекции, частое использование центральных венозных катетеров, имплантация электрокардиостимуляторов и дефибрилляторов, усугубляющих риск инфекционных осложнений и, в целом, формирование протромботического статуса.…”
Section: Discussionunclassified
“…Основными патогенетическими механизмами повышения риска ВТЭО у госпитализированных пациентов с сердечно-сосудистой патологией могут быть эндотелиальное повреждение и эндотелиальная дисфункция, нарушение работы антикоагулянтной системы протеина С при повышенной концентрации в плазме провоспалительных цитокинов (интерлейкин-6, фактор некроза опухоли и др. ), активация PAR-рецепторов, стаз крови в условиях снижения сердечного выброса, повреждение тканей с экспрессией тканевого фактора, запускающего коагуляционный каскад, замедление фибринолиза [10]. Дополнительными факторами риска ВТЭО при ХСН могут являться: пожилой возраст, иммобилизация, инфекции, частое использование центральных венозных катетеров, имплантация электрокардиостимуляторов и дефибрилляторов, усугубляющих риск инфекционных осложнений и, в целом, формирование протромботического статуса.…”
Section: Discussionunclassified
“…The exact cause of venous ulcers is not certain, but a common denominator is generally venous stasis, which may be caused by chronic venous insufficiency, and/or congestive heart failure. 20,21 Venous stasis causes the pressure in veins to increase. The body needs the pressure gradient between arteries and veins in order for the heart to pump blood forward through arteries and into veins.…”
Section: Discussionmentioning
confidence: 99%
“…23 Allowing blood to flow back into the limb, for example by elevating it, is necessary but also contributes to reperfusion injury. 20 Other comorbidities may also be the root cause of venous ulcers. 21 It is in the crus that the classic venous stasis ulcer occurs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, D‐dimer is as a fibrin degradation product; hence, it is relatively commonly used in the diagnostic tree for DVT, and even as a marker in the follow up of PTE. However, reduced cardiac function is considered an intermediate risk factor for venous thromboembolism, including DVT and PTE, which are associated with worse outcomes of heart failure. In our study, the D‐dimer level was found to be a better predictor of all‐cause death in patients with HFPEF than in patients with HFREF, partly because more patients with HFPEF also had atrial fibrillation (AF) .…”
Section: Discussionmentioning
confidence: 99%